NEW INSIGHTS INTO BALINESE PROVERBS: A SYNTACTIC PERSPECTIVE - Radha Andhra Swari; Ika Nurhayani; Sri Endah Tabiati (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
This study investigated two syntactic aspects of Balinese proverbs, namely sentence types and sentence functions. Descriptive qualitative method was applied in this study. The data were obtained from a Balinese proverbs book entitled Paribasa Bali by Ginarsa (2009), and analyzed based on Mac Coinnigh’s framework (2015). The results revealed that a number of Balinese proverbs have simple sentence type, while few of which have complex, compound, and compound-complex sentence type. Additionally, not all Balinese proverbs can be considered as a sentence, since some of which appear in the form of incomplete sentence and dependent clause. Meanwhile, in terms of sentence functions, the most common form among Balinese proverbs is declarative/indicative function, followed by some interrogatives, imperatives, and few combinations of two sentence functions. These findings indicate that Balinese people are more likely to use simple sentence and declarative/indicative function when it comes to passing proverbs in everyday context. However, it is also implied that Balinese people have the tendency to employ various types and functions of proverbs for specific purposes, such as performance and religious purposes.